Reflections on cuban dissidence (2009)
Since the raids of Spring 2003, international press has put dissidents in the forefront of news about Cuba. From the outside, one might believe that the dissidents have a strong gri p on “civil society” and that they represent the democratic future. However, the radical brutality that broke out over these opponents, who the regime describes as “mercenaries at the Empire’s service,” is not the only dimension hindering their movement. We cannot understand the manner in which they have been ignored and engulfed without reconstructing the context of a society immersed within the opaque universe of the “lucha”, the weight of a social imaginary obsessed by “intrigue,” and the effect of official propaganda. The political paradigms in which they are inscribed also share with the Castrist matrix a culture rooted in long-term national history, which exalts the virtues of homogeneity, unanimity and enlightened elitism.Translation Alberto Valencia Gutiérrez, Professor Universidad del Valle in Cali Colombia.